ANALISIS SEMIOTIKA PADA NILAI MORAL DALAM NOVEL DIA ADALAH KAKAKKU KARYA TERE LIYE DAN PEMANFAATANNYA SEBAGAI MODUL PEMBELAJARAN NOVEL DI SMA - Rina Agustina (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study discusses the Semiotic Analysis of Moral Values in the Novel Dia Adalah Kakakku by Tere Liye and its Use as a Learning Module for Interpretation of Novel Text Meanings in SMA/SMK/MA. The purpose of this study is to describe the moral values contained in Tere Liye novel Dia Adalah Kakakku and to describe the use of moral values in Tere Liye's novel Dia Adalah Kakakku as a learning module for interpreting the meaning of novel texts in SMK/MA/SMA.  This research is a qualitative research using a semiotic approach. The data collection technique used in this study is the listening and note-taking technique. The subject of this research is the novel Dia Adalah Kakakku by Tere Liye. The instrument used in this research is a data card. The validity of the data was obtained through triangulation of theories, methods, and data sources. The problem in this study is that at this time the morals of the nation's children tend to be not good. The results of the study reveal that in the novel Dia Adalah Kakakku by Tere Liye there are four types of moral values, namely the human relationship with God consisting of morals towards God and knowing God, the relationship between humans and themselves consists of fighting power and diligence, human relationships with other humans consist of  kinship, help, mutual cooperation, courtesy, keeping promises, and forgiving and human relations with nature consist of taking out trash and caring for plants.  With regard to learning literature in schools, the results of this analysis can be used as material or learning materials in SMA/SMK/MA and these moral values can be used as examples in schools.Key word: Moral values, Dia Adalah Kakakku novel, Literature learning.